AMICABLE AS THE PRINCIPAL MISSION IN A DISPUTE RESOLUTION THROUGH SHARIA ARBITRATION - Dr. Muhammad Arifin S.H., M.Hum (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA)
Feud or dispute which occurs in legal relation of a commercial contrak such as in trade and investment usually cannot be settled to help settle it.